AGE-RELATED CHANGES IN HUMAN SKIN: HISTOLOGICAL, MORPHOMETRIC AND IMMUNCYTOCHEMICAL STUDY USING S100 (Iraqi Journal of Medical Sciences, 2016)
Background:Aging has many effects on a person’s skin, from wrinkles and sags to increased risk of certain skin conditions, such as skin cancer. As people age, their skin begins to change due to environmental, genetic, nutrition and other factors.Objectives:Understand some of the changes that occur in aging skin including changes in the general morphological, histological and architectural arrangement, epidermal thickness, basement membrane and histochemical changes in melanocytes.Methods:Skin specimens were taken from the anterior abdominal wall of 30 human males at different ages. General histological preparation for paraffin blocks was performed and the blocks were sectioned at (5-6µ) and stained with H&E. S100 protein was used to demonstrate immunohistochemistry labeled melanocytes changes with age. Histometric measurement of epidermal thickness and basement membrane thickness, using eyepiece graticule was performed on these groups.Results:The young age group showed a uniform arrangement of cells in all stratums of the epidermis while the old age group showed diminished thickness of the epidermis. A significant difference between young- adult age group (A and B groups) and the old age group (C group) was recorded. The epithelial basement membrane thickness was increased with age significantly (P value ? 0.001). Melanocytes demonstration using S100 showed that these cells tend to be situated at the tips of rete pages, there number are generally low and didn't varied a lot between young and adult age groups. There was yet marked decline in the number of melanocytes in old age group.Conclusion:Aging as a process have a marked influences on skin morphology, thickness, cellularity and basement membrane.Key Words:Aging, skin, S100, morphometry and basement membrane
Keywords: Aging; skin; S100; morphometry and basement membrane